Design, Synthesis and Evaluation of Functionalized Azaglycinamides as Cytotoxic and Antinociceptive Agents: Functionalized Azaglycinamides as Cytotoxic and Antinociceptive Agents - Begum Shaik, Arifa; Begum, Shaheen; Dodoala, Sujatha; Koganti, Bharathi (Iranian Journal of Pharmaceutical Sciences, 2021)
Aza analogs of peptides are used in the treatment of cancer and neurodegenerative disorders. The clinical approval of goserelin for the treatment of prostate cancer proves the therapeutic potentiality of azaglycine residue. With this background, a novel approach to functionalizing the azaglycine moiety aimed at compounds possessing C-functionalization with active five membered heterocycles (pyrrole, imidazole, etc thiazolidine-2, 4-dione) and N-functionalization with acyl chains on azaglycine moiety were synthesized. The compounds were evaluated for in vitro MAGL inhibition and cytotoxicity against MCF-7 cell lines. The biological activities were corroborated with molecular docking studies with Cathepsin B and MAGL enzymes. The compounds with prominent in vitro and in silico potential against MAGL were evaluated for antinociceptive activity. This privileged N- and C-functionalization approach in the synthesis of azaglycinyl analogs demonstrated that N-oleoyl and C-thiazolidine-2,4-dione functionalized azaglycinamide derivative 1q, was found to possess moderate cytotoxic and MAGL inhibitory profile. The active compounds were well accommodated in the binding sites of these targets with good electrostatic complementarity. The N-oleoyl and C-thiazolidine-2, 4-dione functionalized azaglycine can be envisaged as a novel molecule with potential anticancer and antinociceptive activities.